Attitudes toward and willingness to work with older people among undergraduate nursing students in a public university in Sri Lanka: A cross sectional study - Sarath, Rathnayake; Yamuna, Athukorala; Sidiah, John Siop (Elsevier Ltd., 2016)
Background:With the increased number of older people globally, caring for older people has become a challenge for many countries. Nurses have a pivotal role in providing quality care for older people and care is affected by their attitudes. The preparation of nurses to deliver quality care needs to be instilled during their studying in the Schools of Nursing. Objective: To examine the attitudes of nursing students toward and theirwillingness toworkwith older people in Sri Lanka. Methodology: A purposive sample of 98 first to fourth year undergraduate nursing students in the Department of Nursing, University of Peradeniya completed a self-administered questionnaire consisting of socio-demographic variables, Kogan's Attitudes toward Older People Scale, and questions related to willingness to work with older people. Results: Fifty percent of the respondents (n=49) held slightly positive attitudes toward older people while 45% (n= 44) held slightly negative attitudes. About one-third of the respondents (29.9%, n =29) selected the elderly group as the least preferred group for their future career from the categorized seven age groups. Only 5.1% (n = 5) of the respondents ranked the elderly group as the first preferred group. There was a significant difference in attitudes between students who lived with older people and students who did not live with older people (t = 2.565, p = .012). There was a positive relationship between attitudes and preference for working with older people (r = .342, p = .001). Conclusion: Nursing students havemoderately positive attitudes toward older people; however, they show little interest in working with older people. Living with older people develops positive attitudes of young people toward older people. Attitudes are related to the selection in area of specialty in nursing. Nursing curricula need to include Gerontological Nursing as a major area.